2015
DOI: 10.2105/ajph.2015.302763
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Psychosocial Factors Associated With Psychological Distress and Resilience Among Transgender Individuals

Abstract: With different factors identified for psychological distress and resilience, these findings may help inform the development of tailored mental health interventions and resilience-building programs for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
167
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 42 publications
15
167
1
7
Order By: Relevance
“…(20) The results of our study also showed that 78.3% of respondents did not receive family support, 64.1% did not receive social support, and 36% had extreme family relations. This study is in accordance with the study by Simon et al (21) which showed that 74% of gender dysphoric individuals did not have family support, 59.2% were not socially supported, and 27% had extreme family relations. Gender dysphoric individuals who do not get family or social support have a greater risk of depression and suicidal ideation than those who get family or social support.…”
Section: Discussionsupporting
confidence: 93%
“…(20) The results of our study also showed that 78.3% of respondents did not receive family support, 64.1% did not receive social support, and 36% had extreme family relations. This study is in accordance with the study by Simon et al (21) which showed that 74% of gender dysphoric individuals did not have family support, 59.2% were not socially supported, and 27% had extreme family relations. Gender dysphoric individuals who do not get family or social support have a greater risk of depression and suicidal ideation than those who get family or social support.…”
Section: Discussionsupporting
confidence: 93%
“…Community creates social support and fosters love, not just love specific to physical intimacy, but love that is specific to self-appreciation and values related to resiliency and transcendence, as noted in positive psychology theories. To illustrate the importance of specific social support, a study conducted in a national sample of 169 transgender Australians showed that transgender individuals having frequent contact with LGBT peers, having higher income, and identifying as heterosexual showed greater resilience (Bariola et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the case of transsexuals, these attitudes-including refusal of care and harassment or violence in medical settings [69]-could be notably critical, considering the frequency of transsexuals' contact with public hospitals (e.g., psychometric and clinical evaluations). Therefore, they are probably in a highly vulnerable condition, in which contact with informed, empathic, and welcoming professionals could provide psychosocial support and prevent psychological distress and other poor outcomes for general health [37,40].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning transphobia, different studies showed that also transgender individuals reported frequent experiences of violence and discrimination, which they ascribed to their belonging to a sexual minority group [37][38][39][40][41]. There is some evidence to support the idea that, among sexual minorities, transgender people are the most stigmatized, as they clearly violate the rules concerning gender roles [38,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%